1997
DOI: 10.1161/01.atv.17.10.2192
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in the Effects of Testosterone and Estrogen on the Development of Atherosclerosis in Rabbits

Abstract: The aim of the present study was to investigate whether there are gender-specific differences in the effects of testosterone and estrogen on the process of atherogenesis. Thirty-two castrated male and 32 ovariectomized female rabbits were separated into 4 study groups of 8 males and 8 females each and received postoperatively a 0.5% cholesterol diet for 12 weeks. During this period either no hormones, estradiol (1 mg/kg body wt/week), testosterone (25 mg/kg body wt/week IMM), or estrogen combined with testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 40 publications
3
69
1
1
Order By: Relevance
“…Testosterone in male rabbits had an inhibitory effect on plaque development, but in female rabbits, an atheroprogressive action of testosterone was found. 2 These findings indirectly provide support for the hypothesis that arterial sex hormone receptors are probably involved as one part of the genomic actions of sex steroids on the level of the arterial vessel wall. 11 Androgen and estrogen receptors are present in vascular smooth muscle cells, 11,12 human macrophages, human megakaryocytes, and platelets.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Testosterone in male rabbits had an inhibitory effect on plaque development, but in female rabbits, an atheroprogressive action of testosterone was found. 2 These findings indirectly provide support for the hypothesis that arterial sex hormone receptors are probably involved as one part of the genomic actions of sex steroids on the level of the arterial vessel wall. 11 Androgen and estrogen receptors are present in vascular smooth muscle cells, 11,12 human macrophages, human megakaryocytes, and platelets.…”
Section: Discussionmentioning
confidence: 58%
“…Using data from previous animal studies, 2,3 it was postulated that genomic actions are involved in mediating the protective effects of testosterone in the process of atherosclerosis. We hypothesized that vascular androgen receptors might play an important role in signaling the testosterone effects on the level of the arterial vessel wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…111,112 Results from experimental studies show a similar pattern. Bruck et al 113 showed an increase in plaque size after testosterone treatment in female rabbits on an atherogenic diet. This increase was independent of changes in plasma lipids.…”
Section: Atherosclerosismentioning
confidence: 99%
“…[89][90][91] Effects of testosterone on animal models of atherosclerosis and neointima formation It has been demonstrated that the administration of testosterone in castrated male rabbits that were fed a high-cholesterol diet reduced aortic atherosclerosis, largely independent of plasma lipids. 92,93 In addition, neointima formation after coronary balloon injury in swine was increased by castration and was reversed by testosterone replacement. 94 Regarding the role of AR, conflicting findings have been reported.…”
Section: Direct Effects Of Testosterone On Vascular Wallsmentioning
confidence: 99%